The Level of Student Religiosity Seen from the Participation in Rohis at SMA Negeri 2 Bantul - Akhmad Ramadhan; Muthia Umi Setyoningrum (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
As individuals, students will experience social life in society. Free interaction and moral decadence pose a threat to the social life of the student community. Islamic Religious Education (PAI) is expected to be a solution to dealing with these threats. However, the limited learning hours of only three hours were deemed insufficient to achieve the goals of PAI. The alternative is to organize an Islamic spiritual organization. This study aimed to describe the level of religiosity of members and non-members of Rohis as well as empirically test to determine the differences between Rohis and non-Rohis members in religiosity. This study used a quantitative approach with the subject of 23 students of Rohis members and 223 students of non-Rohis members, consisting both female and male, in the age range of 15-18 years old. Primary data was collected through a questionnaire with the Linkert scale technique. Data analysis used the Independent Sample t-Test. The research results obtained: (1) the level of religiosity of Rohis members at SMA Negeri 2 Bantul has an average value of 104.64 and it is a medium category. (2) The level of religiosity of non-Rohis members at SMA Negeri 2 Bantul has an average value of 101.47 in the medium category. Participation in Rohis will affect the level of religiosity of students, so spiritual activities need to be optimized at schools. The school needs to provide guidance and direction to spiritual organizations (Rohis) through general and special da'wah so that the religiosity